A new design of 5G multilayers planar antenna with the enhancement of bandwidth and gain - Abderrahim Bellekhiri; Noha Chahboun; Jamal Zbitou; Yassin Laaziz; Ahmed El Oualkadi (Institute of Advanced Engineering and Science, 2023)
In this work, we design a microstrip patch antenna having a dimension of 3.279x4.232 mm2 and consisting of a Foam-like substrate, of a relative dielectric permittivity of 1 and with a width of 0.5 mm, placed between two identical Rogers RT5880 substrates, having a value of 2.2 as relative dielectric permittivity, a loss tangent of 0.0009 and a height of 0.508 mm. The designed antenna resonates at 28 GHz, featuring a maximum gain of 9.77 dBi and a wide frequency bandwidth of 2.9 GHz. Compared to the conventional antenna, this proposed structure achieved an important enhancement of the directivity, with a value around 38.8°. The CST Microwave Studio software was used for all designs and analysis.